The Influence of Early Drinking Contexts on Current Drinking Among Adult Lesbian and Bisexual Women. (September 2013) - Parks, Cheryl A.; Heller, Nina Rovinelli
BACKGROUND: Differences exist in alcohol-related outcomes across subgroups of sexual minority women. Likewise, stressors associated with coming out and living as lesbian or bisexual are hypothesized to be highly variable. Lesbians' and bisexual women's risks for hazardous drinking are explored in a 2006 NIAAA-funded interview study of women living in the Northeastern United States.OBJECTIVES: The primary objective of the present study is to replicate and extend an earlier analysis of the relationship between early drinking contexts and current drinking outcomes of adult lesbians with a convenience sample that includes a subgroup of self-identified bisexual women. Potential differences in the early drinking contexts of these two groups of self-identified lesbian and bisexual women are also explored.DESIGN: Bivariate and multiple regression analyses are used to examine relationships between early drinking contexts and current drinking of a racially and age-diverse convenience sample of 145 adult lesbian ( N = 94) and bisexually identified ( N = 51) women.RESULTS AND CONCLUSIONS: Consistent with previous research, patterns established while coming out have an enduring effect on drinking outcomes of lesbians; findings for bisexual women are inconclusive. Implications for research and practice are discussed.